Neurodevelopmental impairments in children with septo-optic dysplasia spectrum conditions: a systematic review - Amy Mann; Arameh Aghababaie; Jennifer Kalitsi; Daniel Martins; Yannis Paloyelis; Ritika R. Kapoor (Molecular Autism, 2023)
Abstract Background Septo-optic dysplasia (SOD) is a rare condition diagnosed in children with two or more of the following: hypopituitarism, midline brain abnormalities, and optic nerve hypoplasia. Children with SOD experience varied visual impairment and endocrine dysfunction. Autistic-like behaviours have been reported; however, their nature and prevalence remain to be fully understood. The present systematic review aimed to explore the type and prevalence of neurodevelopmental impairments in children with SOD spectrum conditions. Methods The search was conducted in PubMed, EMBASE, and PsycInfo. Hand-searching reference lists of included studies was conducted. All peer-reviewed, observational studies assessing behavioural and cognitive impairments or autism spectrum disorder (ASD) symptoms in children (< 18 years) with SOD, optic nerve hypoplasia, and SOD-plus were included. Studies were excluded if they did not report standardised measures of neurodevelopmental impairments or ASD outcomes. Results From 2132 screened articles, 20 articles reporting data from a total of 479 children were included in prevalence estimates. Of 14 studies assessing cognitive-developmental outcomes, 175 of 336 (52%) children presented with intellectual disability or developmental delay. A diagnosis of ASD or clinical level of symptoms was observed in 65 of 187 (35%) children across five studies. Only five studies assessed for dysfunction across behavioural, emotional, or social domains and reported impairments in 88 of 184 (48%) of children assessed. Limitations Importantly, high heterogeneity among the samples in relation to their neuroanatomical, endocrine, and optic nerve involvement meant that it was not possible to statistically assess the relative contribution of these confounding factors to the specific neurodevelopmental phenotype. This was further limited by the variation in study designs and behavioural assessments used across the included studies, which may have increased the risk of information bias. Conclusions This systematic review suggests that the prevalence of neurodevelopmental impairments in children within the SOD spectrum may be high. Clinicians should therefore consider including formal assessments of ASD symptoms and neurodevelopmental impairments alongside routine care. There is, additionally, a need for further research to define and validate a standardised battery of tools that accurately identify neurodevelopmental impairments in SOD spectrum conditions, and for research to identify the likely causal mechanisms.